Rendimientos Financieros de la Empresa VECONSA S.A. - Villacís Gavilánez, Ivonne Virginia (2018)
VECONSA S.A. is a company dedicated to the transformation of raw material into elaborated products, and to the elaboration of frozen products using fast freezing techniques, its main source of income is the export of its products. The present work has as its theme "FINANCIAL YIELDS OF THE COMPANY VECONSA SA" whose main objective is to analyze the State of Comprehensive Result of the company since for the years 2016 and September of 2017 it presented a net loss, this was done making comparisons with periods that they cover 2013 to 2015, which in some cases will be carried out on an average basis, as well as analyzing the return on assets and yield on equity of the same years as a result of the performance of the Net Income / Loss. "The financial analysis is of great importance for the proper functioning of the company, and basic in the control of compliance with plans as well as in the study of business results" (Córdoba, 2015) This analysis will be carried out vertically in order to examine, evaluate and explain the financial focus of "VECONSA S.A" within the fiscal periods mentioned above. As it is known that achieving financial performance is one of the fundamental objectives that every organization wants to possess, these returns can be targeted through the performance that the company has been doing. 3 This means that companies are in need of a Financial Analysis.